Implementasi Nilai-Nilai Manajemen Pendidikan Islam Pada Pengelolaan Akun Media Sosial di Pondok Pesantren Modern Darussalam Kepahiang - Tika Dwi Aprilia; Hendra Harmi; Syaiful Bahri (Institusi Agama Islam Negeri (IAIN) Bone, 2026)
The development of information technology has encouraged Islamic educational institutions, including Islamic boarding schools (pesantren), to undergo a transformation in information management through digital media. The problem addressed in this study is how the implementation of Islamic education management values is executed in the management of information systems at Darussalam Modern Islamic Boarding School Kepahiang, particularly regarding management mechanisms, the application of Islamic values, supervision, and their impact on communication and institutional image. This study aims to analyze the implementation of Islamic education management values in information system management as an effort to enhance the effectiveness of delivering Islamic-valued information, transparency, and the strengthening of the school’s image in the community. This study employs a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. Research informants consisted of school leaders, information system managers, and parties involved in managing the school's digital publications. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, with data validity tested using triangulation techniques. The results show that information system management at Darussalam Modern Islamic Boarding School Kepahiang is carried out through the stages of planning, execution, monitoring, and evaluation. The implementation of Islamic education management values is reflected in the application of values such as trustworthiness (amanah), deliberation (musyawarah), responsibility, discipline, professionalism, and Islamic communication ethics in managing digital information. The information system functions not only as a publication medium for school activities but also as a vehicle for digital da'wah (proselytizing), community communication, and establishing a positive institutional image. The novelty of this research lies in the development of an information system management model for Islamic boarding schools that integrates modern management functions with Islamic values, ensuring that digital media management is oriented not only toward information effectiveness but also toward moral, ethical, and Islamic responsibility aspects.